Digital Technologies and the Energy Transition: Integrating ICT for Sustainable Development Goals - Feki, Rochdi; Abdelkafi, Ines; Arous, Chaima (International Journal of Energy Economics and Policy, 2026)
This study investigates the influence of Information and Communication Technologies (ICT) on sustainable development within the framework of the Environmental Kuznets Curve (EKC) hypothesis in the context of European Economic Area (EEA) countries. Specifically, it evaluates how ICT integration into the energy sector contributes to the achievement of Sustainable Development Goals (SDGs). The analysis focuses on 13 EEA countries over the period 2005–2024 and employs a Panel Vector Autoregression (Panel-VAR) model. The central hypothesis is that ICT adoption can serve as a pivotal driver of sustainability, not only by enhancing energy efficiency but also by fostering digital innovation and reducing environmental degradation. The empirical results confirm the existence of a modified EKC in the EEA context and show that ICT has a positive, statistically significant long-run impact on sustainability indicators. In particular, ICT supports the development of smart energy systems that enable more efficient production, consumption, and storage of energy, thereby reducing CO₂ emissions. This paper makes a novel contribution by integrating digital transformation into the EKC framework and highlighting bidirectional relationships between ICT, the energy transition, and sustainable development. The findings offer valuable policy implications, suggesting that investments in digital infrastructure and energy innovation can play a crucial role in achieving long-term sustainability objectives across the EEA region.